45,X/46,XY Mosaicism and Normozoospermia in a Patient with Male Phenotype - Shathmigha Ketheeswaran; Birgit Alsbjerg; Preben Christensen; Claus Højbjerg Gravholt; Peter Humaidan (Case Reports in Medicine)
The phenotypic spectrum of 45,X/46,XY mosaic males varies greatly. Previous reports have only described cases with either oligozoospermia, growth retardation, or elevated gonadotropins. However, the present case presented with normozoospermia, and normal height, sperm DNA fragmentation index (DFI), and gonadotropins. The male and his spouse were referred to The Fertility Clinic, Skive Regional Hospital, due to 2 years of infertility. After failure of several attempts of assisted reproductive treatment (ART), the male underwent genetic analysis. Conventional karyotyping in peripheral lymphocytes yielded a low-grade 45,X/46,XY mosaicism, confirmed by fluorescence in situ hybridization (FISH) showing 6% 45,X cells. A FISH test performed on interphase nuclei from buccal mucosal cells yielded one cell with only one X-signal (0.6%), explaining the normal phenotype of the patient, but not the infertility. FISH test for sperm aneuploidy showed normal range parameters, except for a 10-fold elevated gonosomal nullisomy rate (2.1%). Hence, germinal mosaicism may be an explanation of the infertility of the case. Increased sex nullisomy levels may reflect an aberrant testicular environment compromising fertility even though sperm euploidy rates and other sperm parameters do not preclude a successful treatment with ART. Based on these results, the couple decided to use donor semen for their subsequent intrauterine insemination treatment and obtained a successful pregnancy.